2016
DOI: 10.1098/rsos.160577
|View full text |Cite
|
Sign up to set email alerts
|

Alloparenting is associated with reduced maternal lactation effort and faster weaning in wild chimpanzees

Abstract: Alloparenting, when individuals other than the mother assist with infant care, can vary between and within populations and has potential fitness costs and benefits for individuals involved. We investigated the effects of alloparenting on the speed with which infants were weaned, a potential component of maternal fitness because of how it can affect inter-birth intervals, in wild chimpanzees (Pan troglodytes schweinfurthii) at Ngogo, Uganda. We also provide, to our knowledge, the first description of alloparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 107 publications
(273 reference statements)
1
35
0
Order By: Relevance
“…Plant and animal tissues vary isotopically in characteristic ways, and the carbon (δ 13 C) and nitrogen (δ 15 N) isotope signatures of a consumer's tissues, including soft tissues, mineralized tissues, and excreta, reflect the isotope ratios of its foods 14,17,18 . Broadly, δ 13 C values reflect the photosynthetic pathways of plants, differentiating plants into C 3 , C 4 , and Crassulacean acid metabolism (CAM) categories, and δ 15 N values reflect trophic position, including faunivory and weaning 16,19–22 . To a lesser extent, both δ 13 C and δ 15 N values in plants reflect temporal and spatial differences in habitats, 23,24 and δ 13 C values, like δ 15 N values, have been informative of weaning 20,21,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Plant and animal tissues vary isotopically in characteristic ways, and the carbon (δ 13 C) and nitrogen (δ 15 N) isotope signatures of a consumer's tissues, including soft tissues, mineralized tissues, and excreta, reflect the isotope ratios of its foods 14,17,18 . Broadly, δ 13 C values reflect the photosynthetic pathways of plants, differentiating plants into C 3 , C 4 , and Crassulacean acid metabolism (CAM) categories, and δ 15 N values reflect trophic position, including faunivory and weaning 16,19–22 . To a lesser extent, both δ 13 C and δ 15 N values in plants reflect temporal and spatial differences in habitats, 23,24 and δ 13 C values, like δ 15 N values, have been informative of weaning 20,21,25 .…”
Section: Introductionmentioning
confidence: 99%
“…This study shows that infant handling in wild mountain gorillas occurs at a rate of 0.05 bouts per observational hour and is thus a relatively infrequent behavior in the behavioral repertoire of this species. To put this result in context: observations of infant handling in captive bonobos occurred at a rate of 0.68 per hour (Boose, White, Brand, Meinelt, & Snodgrass, ) and in wild chimpanzees at a rate of 0.12 bouts per hour (Bădescu, Watts, Katzenberg, & Sellen, ). Infant handling is also far less common than other social behaviors such as grooming (rate: 0.82 events per hour) and playing (0.83 events per hour) in this population.…”
Section: Discussionmentioning
confidence: 99%
“…First, frequent alloparenting may offer mothers more opportunities to feed freely without being encumbered by their infants; this may boost the mothers' net energy gains. Second, frequent alloparenting may lead to faster weaning because infants who are provided with more alloparenting face longer periods between nursing bouts than infants who are regularly in contact with the mother's nipple; this expedites resumption of cycling for mothers (Bădescu, Watts, Katzenberg, & Sellen, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These benefits may include a ‘safe’ social partner such that mothers with juvenile offspring would not need to engage in as much social interaction with their own infants or spend time in parties with other potential social partners, which could allow for mothers to focus on feeding in the absence of other competitors. A recent study among mother-infant pairs in the Ngogo chimpanzee community in Uganda found that increases in infant handling by non-mothers was related to lower lactation effort, which the authors suggest could be indicative of faster weaning and shorter interbirth intervals (IBIs) (Badescu et al, 2016). Early work in Gombe National Park, Tanzania also found descriptive evidence suggesting that mothers with two dependent offspring spend less time with other mothers than mothers with one dependent offspring (Halperin, 1979) and statistical evidence that infants with siblings spent less time interacting with other community members than infants without siblings (Brent et al, 1997).…”
Section: Introductionmentioning
confidence: 99%